ОНА ТИЛИНИ ЎҚИТИШ ЖАРАЁНИДА ИННОВАЦИОН ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИШНИНГ АҲАМИЯТИ - Ибрагимов, Ю.М.; Ибрагимова, У.Ю. (SCIENCE and SOCIETY, 2016)
The article deals with the opinions, discussions and suggestions about the ways of using innovative technologies to improve the knowledge, habits and skills of students about the interaction and differences in the lexical, semantic, grammatical, stylistic and functional peculiarities in the Uzbek language.